Optimizing monocyte-derived immune cell cultures: comparing xeno-free and xenogeneic conditions - Marek, Nora; Wolff, Anette S. B.; Dongre, Harsh N.; Suliman, Salwa (Frontiers in Immunology, 2025)
Culture conditions significantly affect the phenotype of immune cells. This study compared, for the first time, the impact of xeno-free human AB serum and xenogeneic fetal bovine serum (FBS) culture conditions on the surface marker expression of monocyte-derived macrophages (Mo-Mø) and dendritic cells (Mo-DC) using spectral flow cytometry. Monocytes were differentiated into macrophages or Mo-DC over 6 days. M0 macrophages were polarized toward M1-like or M2-like macrophages, and Mo-DC were activated using LPS. Differentiation was successful in both conditions. Despite cells exhibiting autofluorescence, distinct phenotypes based on selected differentiation markers were observed. CD1a expression was lacking in AB cultures, while expression of CD16, CD163 and the co-stimulatory molecules CD80 were significantly upregulated and CD86 downregulated by xenogeneic FBS conditions. These novel findings highlight the need for careful selection of serum type and phenotyping markers to minimize unexpected results and account for potential serum-induced interference with marker expressions in monocyte-derived immune cells.